PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Meindro Waskito (Jurnal Manajemen Bisnis dan Keuangan, 2020)
PT Denso Ten Manufacturing Indonesia is a manufacturing company established in 2012, PT Denso Ten Manufacturing Indonesia manufactures Infotainment (CD tuner) and Car Electronic Devices, such as:Car audio, video, navigation and control systems. This Research aims to determine the influence of work disciplineon employee performance Part Of the SMT Process P there IS PT Denso Ten Manufacturing Indonesia. This type ofresearch is quantitative with an associative method with a level of α significance = 0.05 (5%) and 95% confidencelevel. The population in this research is an employee of the SMT Process. While the sample used as much as 38 people. The technique used by the authors in determining the samples in this study is non-probability sampling by thesaturation sampling method whereby the entire population was made samples. The data collection techniques in thisstudy are by interviews, observations, questionnaires, and literature studies. Instrument testing using validity testsand reliability tests, and for data analysis methods using frequency distribution analysis, simple linear regression,correlation coefficient, coefficient of determination, and t test. Data calculations are done manually and using SPSSversion 21. The simple linear Regression equation gained in this study was Y = 8.504 + 1, 248X . Test results obtainedby value R (coefficient of correlation) performance with working discipline of 0, 707 and R Square = 0, 500 and asignification value of 0.001 < 0.05 which means that 50 % of employee performance is influenced by work disciplinewhile the remaining 5 0 % are influenced by other factors that are not addressed in this study. It is evidenced by the value t Count 5.998 t value of the table was 2.028 so Ho was rejected and Ha accepted. This means that there is asignificant influence between the work discipline and the employee performance of the SMT Process at PT Denso TenManufacturing Indonesia.